21-Hydroxypregnane 21-O-malonylation, a crucial step in cardenolide biosynthesis, can be achieved by substrate-promiscuous BAHD-type phenolic glucoside malonyltransferases from Arabidopsis thaliana and homolog proteins from Digitalis lanata - Tropper, Marina; Höhn, Stephanie; Wolf, Laura-Sophie; Fritsch, Julia; Kastner-Detter, Nina; Rieck, Christoph; Munkert, Jennifer; Meitinger, Nadine; Lanig, Harald; Kreis, Wolfgang (Phytochemistry, 2021)
Three putative 21-hydroxypregnane 21-O-malonyltransferases (21MaT) from Digitalis lanata were partially purified.Two of them were supposed to be BAHD-type enzymes. We were unable to purify them in quantities necessary for reliable sequencing. We identified two genes in A. thaliana coding for substrate-promiscuous BAHDtype phenolic glucoside malonyltransferases (AtPMaT1, AtPMaT2) and docked various 21-hydroxypregnanes into the substrate-binding site of a homology model built on the BAHD template 2XR7 (NtMaT1 from N. tabacum). Recombinant forms of Atpmat1 and Atpmat2 were expressed in E. coli and the recombinant enzymes characterized with regard to their substrate preferences. They were shown to malonylate various 21-hydroxypregnanes. The Atpmat1 sequence was used to identify candidate genes in Digitalis lanata (Dlmat1 to Dlmat4). Dlmat1 and Dlmat2 were also expressed in E. coli and shown to possess 21-hydroxypregnane 21-O-malonyltransferase activity.<br
Keywords: Digitalis lanata; Plantaginaceae; Foxglove; Protein purification; Protein modeling; Gene expression analysis; Cardenolides; BAHD; Pregnane 21-O-malonyltransferase

BAHD-like malonyltransferase genes from Digitalis lanata and Arabidopsis thaliana and their putative role in cardenolide biosynthesis - Tropper, Marina; Höhn, Stephanie; Munkert, Jennifer; Kreis, Wolfgang (PLANTA MEDICA, 2019)
CRIS-Team WoS Importer:2020-01-10

In silico, in vitro, and structural investigations on BAHD-enzymes from different species able to malonylate 21-hydroxypregnanes - Tropper, Marina; Wolf, Laura-Sophie; Lanig, Harald; Kreis, Wolfgang (PLANTA MEDICA, 2021)
CRIS-Team WoS Importer:2021-12-31

Knockout of arabidopsis thaliana vep1, encoding a prise (Progesterone 5β-reductase/iridoid synthase-like enzyme), leads to metabolic changes in response to exogenous methyl vinyl ketone (mvk) - Klein, Jan; Ernst, Mona; Christmann, Alexander; Tropper, Marina; Leykauf, Tim; Kreis, Wolfgang; Munkert, Jennifer (Metabolites, 2022)
Small or specialized natural products (SNAPs) produced by plants vary greatly in structure and function, leading to selective advantages during evolution. With a limited number of genes available, a high promiscuity of the enzymes involved allows the generation of a broad range of SNAPs in complex metabolic networks. Comparative metabolic studies may help to understand why—or why not—certain SNAPs are produced in plants. Here, we used the wound-induced, vein patterning regulating VEP1 (AtStR1, At4g24220) and its paralogue gene on locus At5g58750 (AtStR2) from Arabidopsis to study this issue. The enzymes encoded by VEP1-like genes were clustered under the term PRISEs (progesterone 5β-reductase/iridoid synthase-like enzymes) as it was previously demonstrated that they are involved in cardenolide and/or iridoid biosynthesis in other plants. In order to further understand the general role of PRISEs and to detect additional more “accidental” roles we herein characterized A. thaliana steroid reductase 1 (AtStR1) and compared it to A. thaliana steroid reductase 2 (AtStR2). We used A. thaliana Col-0 wildtype plants as well as VEP1 knockout mutants and VEP1 knockout mutants overexpressing either AtStR1 or AtStR2 to investigate the effects on vein patterning and on the stress response after treatment with methyl vinyl ketone (MVK). Our results added evidence to the assumption that AtStR1 and AtStR2, as well as PRISEs in general, play specific roles in stress and defense situations and may be responsible for sudden metabolic shifts.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Arabidopsis thaliana; Reactive electrophile species; Specialized metabolism; Steroid reductase